APPLICATION OF THE PJBL MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN HISTORY SUBJECTS AT SMA N 2 PALEMBANG - Salsabilah, Nara Shakti; Hudaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research examines the application of the Project-Based Learning (PJBL)learning model in an effort to improve student learning outcomes in the Historysubject at SMA N 2 Palembang. The PJBL model is a learning approach that placesstudents at the center of learning activities through projects that challenge them tosolve problems independently or in groups. This model is designed to increaseactive student engagement and provide a deeper learning experience. In thisresearch, the method used is a combination of literature study and directobservation. A literature study was conducted to understand the basic concepts andimplementation of the PJBL model, as well as to identify effective strategies forimplementing it in the classroom. Meanwhile, direct observation was used to see inreality how the PJBL model was applied in the context of history learning at SMA N2 Palembang. The results of observations show that implementing PJBL in Historyclasses can increase student interest and participation in the learning process.Students become more enthusiastic in following lessons and more active in groupdiscussions. They also show improvements in critical thinking skills, analysis, andcomplex problem solving abilities. Thus, implementing PJBL not only improvesacademic learning outcomes, but also develops important skills needed in everydaylife. This research concludes that the PJBL model is an effective approach toimproving the quality of history learning in schools, and is able to encouragestudents to learn in a more meaningful and relevant way.